Ontogenic Profile of Gluconeogenic Key Enzyme Gene Expressions in Embryonic Chicken Liver and Muscle - Tushar K. Roy; Atsushi Iwasawa; Yasutake Shimizu; Koji Kageyama; Norio Yoshizaki (The Journal of Poultry Science, 2013)
To elucidate biochemical mechanisms underlining high plasma glucose in chicken embryo, gene expression profile of gluconeogenic key enzymes were characterized. The liver and skeletal muscle were collected from 13- to 21-day embryos (E) (n＝8) of layer chicken and the mRNA of pyruvate carboxylase (PC), cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C), mitochondrial phosphoenolpyruvate carboxykinase (PEPCK-M), muscle-type fructose-1,6-bisphosphatase (mFBPase), liver-type fructose-1,6-bisphosphatase (lFBPase) and glucose-6-phosphatase (G6Pase) were measured by real-time PCR. All the enzymes were expressed in the liver, whereas in the skeletal muscle, only mFBPase and G6Pase were detected. In the liver, all the enzymes except for G6Pase peaked either on E13 or E15. G6Pase expression was the highest between E15 and E19. In the skeletal muscle, mFBPase peaked on E19 and G6Pase peaked on E15. These results suggest that gluconeogenesis is active in chicken embryos but regulations of mRNA expressions of the gluconeogenic key enzymes are different between liver and muscle. The results also suggest that the skeletal muscle, which is generally not regarded as a tissue conducting an active gluconeogenesis, may contribute to the regulation of embryonic plasma glucose to some extent, and warrant further investigations of the presence of enzyme activities.